Genetic Polymorphisms of Long Non-coding RNA Linc00312 Are Associated With Susceptibility and Predict Poor Survival of Nasopharyngeal Carcinoma - Guo, Zhen; Bao, Mei-Hua; Fan, Yun-Xia; Zhang, Yan; Liu, Hai-Yan; Zhou, Xiao-Long; Wu, Ben; Lu, Qing-Qing; He, Bin-Sheng; Nan, Xu-Ying; Lu, Jiao-Yang (Frontiers in Cell and Developmental Biology, 2021)
Background: Linc00312 is dysregulated in nasopharyngeal carcinoma (NPC) and participates in the initiation and progression of NPC. Our previous studies suggested that overexpression of linc00312 could sensitize NPC cells to radiation treatment and was associated with better short-term curative effect and overall survival for NPC patients. The single nucleotide polymorphisms (SNPs) of lncRNAs may influence the disease course and outcome by affecting the expression, secondary structure or function of lncRNAs. However, the role of SNPs in linc00312 on the occurrence and survival of NPC remains unknown. Method: 684 NPC patients and 823 cancer-free controls were recruited to evaluate the association between linc00312 SNPs and NPC susceptibility by using multivariate logistic regression analysis. Kaplan-Meier analysis and Cox proportional hazards regression were applied to assess the survival of NPC patients. The relative expression of linc00312 in NPC tissues with different genotypes was determined by real-time PCR. Luciferase reporter assay was used to study the interaction between linc00312 and mir-411-3p. In silico prediction of the changes on linc00312 folding structure was conducted by RNAfold WebServer. Result: We demonstrated that rs12497104 (G>A) was associated with an increased risk of NPC (GA vs GG, OR=1.437, P=0.003). Besides, the rs12497104 AA genotype carriers had a poorer overall survival than GG genotype carriers (AA vs GG, HR=2.117, P=0.011). In addition, rs15734 (A>G) (GA vs GG, OR=0.778, P=0.031) and rs164966 (G>A) (GA vs AA, OR=0.781, P=0.033) were correlated with decreased risk of NPC. We found that the three SNPs might influence the expression of linc00312 in a genotype specific feature and the local folding structures and minimum free energy of linc00312 was changed following the candidate SNPs alterations. Besides, we revealed that the G to A alteration at rs12497104 disrupted the binding between mir-411-3p and linc00312. Conclusion: Our results indicated genetic polymorphisms of linc00312 might serve as potential biomarkers for NPC carcinogenesis and prognosis.